Opportunities and challenges for biosensors and nanoscale analytical tools for pandemics: COVID-19 - Bhalla, Nikhil; Pan, Yuwei; Yang, Zhugen; Payam, Amir Farokh (American Chemical Society, 2020)
Biosensors and nanoscale analytical tools have shown a huge growth in literature in the past 20 years, with a large number of reports on the topic of ’ultra-sensitive’, ’costeffective’ and ’early-detection’ tools with a potential of ’mass-production’ cited on the web of science. Yet none of these tools are commercially available in the market or practically viable for mass production and use in pandemic diseases such as COVID-19. In this context, we review the technological challenges and opportunities of current bio/chemical sensors and analytical tools by critically analyzing the bottlenecks which have hindered the implementation of advanced sensing technologies in pandemic diseases. We also describe in brief COVID-19 by comparing it with other pandemic strains such as SARS and MERS for the identification of features that enable biosensing. Moreover, we discuss visualization and characterization tools that can potentially be used not only for sensing applications but also assist in speeding up the drug discovery and vaccine development process. Furthermore, we discuss the emerging monitoring mechanism, namely wastewater-based epidemiology, for early warning of the outbreak, focusing on sensors for rapid and on-site analysis of SARS-COV-2 in sewage. To conclude, we provide holistic insights into challenges associated with the quick translation of sensing technologies, policies, ethical issues, technology adoption, and an overall outlook of the role of the sensing technologies in pandemics.
Keywords: pandemics; covid-19; poct-devices; electron-microscopy; xrd; afm; microfluidics; sewage-sensors; nanoplasmonics; nanosensors